Shadow Banking and Market Discipline on Traditional Banks. (IMF Working Papers; Working Paper ;, 2017)
We present a model in which shadow banking arises endogenously and undermines market discipline on traditional banks. Depositors' ability to re-optimize in response to crises imposes market discipline on traditional banks: these banks optimally commit to a safe portfolio strategy to prevent early withdrawals. With costly commitment, shadow banking emerges as an alternative banking strategy that combines high risk-taking with early liquidation in times of crisis. We bring the model to bear on the 2008 financial crisis in the United States, during which shadow banks experienced a sudden dry-up of funding and liquidated their assets. We derive an equilibrium in which the shadow banking sector expands to a size where its liquidation causes a fire-sale and exposes traditional banks to liquidity risk. Higher deposit rates in compensation for liquidity risk also weaken threats of early withdrawal and traditional banks pursue risky portfolios that may leave them in default. Policy interventions aimed at making traditional banks safer such as liquidity support, bank regulation and deposit insurance fuel further expansion of shadow banking but have a net positive impact on financial stability. Financial stability can also be achieved with a tax on shadow bank profits.